The Question of “Representation” in the Psychoanalytical and Cognitive-Behavioral Approaches. Some Theoretical Aspects and Therapy Considerations - De Timary, Philippe; Heenen-Wolff, Susann; Philippot, Pierre (Frontiers in Psychology, 2011)
This paper compares the cognitive-behavioural and psychoanalytical approaches with respect to the way in which each of them conceives of representation and deals with the issues that this involves. In both of them conscious and latent (unconscious) representations play a crucial role. Highlighting similarities and differences facilitate communication on a theoretical level but also prove helpful to the clinical practitioners involved. We try to put forward an attempt at comparison, with the idea of going beyond the -- obviously important -- differences in vocabulary. In this attempt at comparison, we have successively compared the definitions of representation and the respective therapeutic interventions proposed by each approach. There are no doubt many overlapping elements in the way in which the workings of the mind are conceived of in these approaches, particularly as regards their links with affects. We next developed the implications of representation deficits in pathology, suggesting the important role played by elements that are avoided, suppressed from memory or repressed, and with respect to the need to treat such material in a specific manner so as to ensure some progress as to the symptoms presented. We finally summarized common and distinct aspects of the two perspectives. The very fact that two approaches that follow very distinct methodologies reach the same conclusion concerning the importance of distortions and failures of representation in generating mental distress strengthens, in our view, the epistemological reliability of the role of representation in psychopathology.